(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Peripheral arterial disease (PAD) is a manifestation of systemic atherosclerosis and is frequently associated with involvement of other vascular territories including the carotid arteries. Patients with PAD are at increased risk of asymptomatic carotid artery stenosis (ACAS), which may predispose them to ischemic stroke and cerebrovascular complications. The present study was conducted to determine the prevalence of ACAS in patients with PAD and evaluate associated risk factors. Methodology: This hospital-based observational study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from February 2025 to January 2026. Patients diagnosed with peripheral arterial disease based on ankle-brachial index (ABI) were included in the study. Carotid duplex ultrasonography was performed using a high-resolution B-mode ultrasound machine with a 7.5 MHz linear-array transducer to assess carotid artery stenosis and plaque characteristics. Clinical variables including age, smoking, diabetes mellitus, hypertension, chronic kidney disease, and coronary artery disease were analyzed. Statistical analysis was performed using Chi-square and Fisher’s exact tests. Results: A total of 147 patients were evaluated, with a mean age of 56 ± 9.72 years, and 87% were males. Smoking and hypertension were highly prevalent among study participants. Multilevel arterial disease was common. Advanced age (>63 years), chronic kidney disease, previous cerebrovascular disease, and ABI <0.4 showed significant association with severe carotid artery stenosis. Carotid duplex ultrasonography effectively identified significant asymptomatic carotid artery disease and vulnerable plaques. Conclusion: Asymptomatic carotid artery stenosis is common among patients with peripheral arterial disease. Carotid duplex ultrasonography is a valuable non-invasive screening tool for early detection of carotid artery disease in high-risk PAD patients.